Clinical Relevance of Home Monitoring of Vital Signs and Blood Glucose Levels: A Narrative Review. (2019) - Lee, Jessica P.; Freeman, Georgina; Cheng, Michelle; Brown, Lauren; De la Hoz Siegler, Hector; Conly, John
Abstract: Objectives: We sought to assess the presence and reporting quality of peer-reviewed literature concerning the accuracy, precision, and reliability of home monitoring technologies for vital signs and glucose determinations in older adult populations. Methods: A narrative literature review was undertaken searching the databases Medline, Embase, and Compendex. Peer-reviewed publications with keywords related to vital signs, monitoring devices and technologies, independent living, and older adults were searched. Publications between the years 2012 and 2018 were included. Two reviewers independently conducted title and abstract screening, and four reviewers independently undertook full-text screening and data extraction with all disagreements resolved through discussion and consensus. Results: Two hundred nine articles were included. Our review showed limited assessment and low-quality reporting of evidence concerning the accuracy, precision, and reliability of home monitoring technologies. Of 209 articles describing a relevant device, only 45 percent ( n = 95) provided a citation or some evidence to support their validation claim. Of forty-eight articles that described the use of a comparator device, 65 percent ( n = 31) used low-quality statistical methods, 23 percent ( n = 11) used moderate-quality statistical methods, and only 12 percent ( n = 6) used high-quality statistical methods. Conclusions: Our review found that current validity claims were based on low-quality assessments that do not provide the necessary confidence needed by clinicians for medical decision-making purposes. This narrative review highlights the need for standardized health technology reporting to increase health practitioner confidence in these devices, support the appropriate adoption of such devices within the healthcare system, and improve health outcomes.